Phenotypic and transcriptomic profiling of induced pluripotent stem cell (iPSC)-derived NK cells and their cytotoxicity against cancers - Nontaphat Thongsin; Siriwal Suwanpitak; Punn Augsornworawat; Jakkrapatra Srisantitham; Kritayaporn Saiprayong; Piroon Jenjaroenpun; Methichit Wattanapanitch (Stem Cell Research & Therapy)
Abstract Background Adoptive immunotherapy using natural killer (NK) cells has attracted considerable interest in numerous clinical trials targeting both hematological and solid tumors. Traditionally, NK cells are primarily derived from either peripheral blood (PB) or umbilical cord blood (UCB). However, these methods can lead to variability and heterogeneity within the NK cell population. In contrast, induced pluripotent stem cell (iPSC)-derived NK (iNK) cells provide a more controlled and uniform cellular population, suitable for large-scale clinical applications. This makes iNK cells a promising option for developing “off-the-shelf” immunotherapeutic products. Nevertheless, current NK cell differentiation protocols, which rely on embryoid body (EB) cultures, are labor-intensive and susceptible to unwanted heterogeneity during differentiation. Here, we developed a more efficient approach for generating iNK cells by employing a monolayer and feeder-free differentiation protocol, alongside optimized culture media. Methods The iNK cells were generated using a two-step in vitro monolayer feeder-free system following NK cell development. To evaluate their maturity, phenotypic analysis was performed using flow cytometry, comparing with PB-NK cells and the NK-92 cell line. Additionally, single-cell RNA sequencing was performed to examine their transcriptomic profiles. The cytotoxic activity of the iNK cells was evaluated by co-culturing with cholangiocarcinoma (CCA) and breast cancer (BCA) cell lines in both monolayer (2D) and tumor spheroid (3D) co-culture systems. Results We successfully differentiated iPSCs into mesoderm (ME), hematopoietic stem/progenitor cells (HSPCs), and NK cells. The resulting iNK cells exhibited typical NK cell markers such as CD45, CD56, and CD16, and expressed key functional proteins, including both activating and inhibitory receptors. Single-cell RNA sequencing confirmed that the transcriptomic profile of our iNK cells closely resembles that of PB-NK cells. Importantly, our iNK cells demonstrated strong cytotoxic abilities against various CCA and BCA cell lines, surpassing the NK-92 cell line in both monolayer cultures and tumor spheroid cultures. Conclusion This study highlights the potential of iPSCs as an effective alternative cell source for generating NK cells. Using a two-step in vitro monolayer feeder-free system, we successfully generated iNK cells that not only expressed key NK cell markers and their receptors but also displayed a transcriptomic profile closely resembling PB-NK cells. Furthermore, iNK cells exhibited cytotoxicity against CCA and BCA cell lines comparable to that of PB-NK cells. This approach could pave the way for off-the-shelf NK cell products, potentially enhancing the effectiveness of adoptive NK cell therapy.